Emerging investigator series: a holistic approach to multicomponent EXAFS: Sr and Cs complexation in clayey soils. Issue 8 (28th June 2021) - Bots, Pieter; Comarmond, M. Josick; Payne, Timothy E.; Gückel, Katharina; Lunn, Rebecca J.; Rizzo, Luca; Schellenger, Alexandra E. P.; Renshaw, Joanna C.
Abstract : Strontium and caesium are fission products of concern at many nuclear legacy sites. In this study we used a novel approach to EXAFS spectra to determine the details of Cs and Sr surface complexation in clayey soils. Abstract : Strontium and caesium are fission products of concern at many nuclear legacy sites and Cs is additionally a significant consideration at sites in the aftermath of nuclear accidents and incidents. Such sites require long-term management to minimize the risk of such contaminants to the environment and the public. Understanding the geochemical speciation of Sr and Cs in situ in the soils and groundwater is essential to develop engineered management strategies. Here we developed and utilized a comprehensive approach to fitting the EXAFS of Sr and Cs adsorption to single mineral phases and a composite clayey soil. First, a shell-by-shell fitting strategy enabled us to determine that Sr surface complexes involve the formation of bidentate edge sharing complexes with anatase and illite-smectite, and form at the silicon vacancy sites at the kaolinite basal surfaces. Cs surface complexes form at the silicon vacancy sites at the illite-smectite and kaolinite basal surfaces. Second, using a subsequent holistic approach we determined the predominance of these complexes within a composite clayey soil. Sr was dominated by complexation with illite-smectite (72–76%) and to a lesser extent with kaolinite (25–30%) with negligible complexation with anatase, while Cs complexed roughly equally to both illite-smectite and kaolinite. The presented approach to fitting EXAFS spectra will strengthen predictive modelling on the behaviour of elements of interest. For example, the details on Sr and Cs speciation will enable predictive modelling to characterise their long-term behaviour and the design and validation of evidence-based engineering options for long-term management of nuclear legacy sites.